Design and facile synthesis of defect-rich C-MoS2/rGO nanosheets for enhanced lithium–sulfur battery performance - Tian, Chengxiang; Wu, Juwei; Ma, Zheng; Li, Bo; Li, Pengcheng; Zu, Xiaotao; Xiang, Xia (Beilstein Journal of Nanotechnology, 2019)
We report a simple one-step hydrothermal strategy for the fabrication of a C-MoS2/rGO composite with both large surface area and high porosity for the use as advanced electrode material in lithium–sulfur batteries. Double modified defect-rich MoS2 nanosheets are successfully prepared by introducing reduced graphene oxide (rGO) and amorphous carbon. The conductibility of the cathodes can be improved through the combination of amorphous carbon and rGO, which could also limit the dissolution of polysulfides. After annealing at different temperatures, it is found that the C-MoS2/rGO-6-S composite annealed at 600 °C yields a noticeably enhanced performance of lithium–sulfur batteries, with a high specific capacity of 572 mAh·g−1 at 0.2C after 550 cycles, and 551 mAh·g−1 even at 2C, much better than that of MoS2-S nanosheets (249 mAh·g−1 and 149 mAh·g−1) and C-MoS2/rGO-S composites (334 mAh·g−1 and 382 mAh·g−1). Our intended electrode design protocol and annealing process may pave the way for the construction of other high-performance metal disulfide electrodes for electrochemical energy storage.
Keywords: annealing; double modification; high-performance electrodes; lithium–sulfur battery; molybdenum disulfide (MoS2); reduced graphene oxide (rGO)

(untitled) - Lei, T.; Chen, W.; Huang, J.; Yan, C.; Sun, H.; Wang, C.; Zhang, W.; Li, Y.; Xiong, J. (Adv. Energy Mater., 2017)

(untitled) - Pu, J.; Shen, Z.; Zheng, J.; Wu, W.; Zhu, C.; Zhou, Q.; Zhang, H.; Pan, F. (Nano Energy, 2017)

(untitled) - Lin, H.; Yang, L.; Jiang, X.; Li, G.; Zhang, T.; Yao, Q.; Zheng, G. W.; Lee, J. Y. (Energy Environ. Sci., 2017)

(untitled) - Pang, Q.; Liang, X.; Kwok, C. Y.; Nazar, L. F. (Nat. Energy, 2016)

(untitled) - Yin, Y.-X.; Xin, S.; Guo, Y.-G.; Wan, L.-J. (Angew. Chem., Int. Ed., 2013)

(untitled) - Wang, A.; Xu, G.; Ding, B.; Chang, Z.; Wang, Y.; Dou, H.; Zhang, X. (ChemElectroChem, 2017)

(untitled) - Hu, G.; Xu, C.; Sun, Z.; Wang, S.; Cheng, H.-M.; Li, F.; Ren, W. (Adv. Mater. (Weinheim, Ger.), 2016)

(untitled) - Fang, M.; Chen, Z.; Liu, Y.; Quan, J.; Yang, C.; Zhu, L.; Xu, Q.; Xu, Q. (J. Mater. Chem. A, 2018)

(untitled) - Wang, J.-Z.; Lu, L.; Choucair, M.; Stride, J. A.; Xu, X.; Liu, H.-K. (J. Power Sources, 2011)

(untitled) - Huang, J.-Q.; Zhang, Q.; Peng, H.-J.; Liu, X.-Y.; Qian, W.-Z.; Wei, F. (Energy Environ. Sci., 2014)

(untitled) - Qie, L.; Manthiram, A. (Adv. Mater. (Weinheim, Ger.), 2015)

(untitled) - Yao, H.; Yan, K.; Li, W.; Zheng, G.; Kong, D.; Seh, Z. W.; Narasimhan, V. K.; Liang, Z.; Cui, Y. (Energy Environ. Sci., 2014)

(untitled) - Jeong, Y. C.; Kim, J. H.; Kwon, S. H.; Oh, J. Y.; Park, J.; Jung, Y.; Lee, S. G.; Yang, S. J.; Park, C. R. (J. Mater. Chem. A, 2017)

(untitled) - Guo, P.; Liu, D.; Liu, Z.; Shang, X.; Liu, Q.; He, D. (Electrochim. Acta, 2017)

(untitled) - Ghazi, Z. A.; He, X.; Khattak, A. M.; Khan, N. A.; Liang, B.; Iqbal, A.; Wang, J.; Sin, H.; Li, L.; Tang, Z. (Adv. Mater. (Weinheim, Ger.), 2017)

(untitled) - Sun, F.; Tang, H.; Zhang, B.; Li, X.; Yin, C.; Yue, Z.; Zhou, L.; Li, Y.; Shi, J. (ACS Sustainable Chem. Eng., 2018)

(untitled) - Li, Z.; Zhang, J.; Guan, B.; Wang, D.; Liu, L.-M.; Lou, X. W. (Nat. Commun., 2016)

(untitled) - Han, S.; Zhu, Y.; Cai, C.; Zhu, J.; Han, W.; Chen, L.; Zu, X.; Yang, H.; Gu, M. (Appl. Phys. Lett., 2019)

(untitled) - Zhang, X.; Lai, Z.; Tan, C.; Zhang, H. (Angew. Chem., Int. Ed., 2016)

(untitled) - Cai, C.; Han, S.; Liu, W.; Sun, K.; Qiao, L.; Li, S.; Zu, X. (Appl. Catal., B, 2020)

(untitled) - Lai, W.; Chen, Z.; Zhu, J.; Yang, L.; Zheng, J.; Yi, X.; Fang, W. (Nanoscale, 2016)

(untitled) - Bruix, A.; Füchtbauer, H. G.; Tuxen, A. K.; Walton, A. S.; Andersen, M.; Porsgaard, S.; Besenbacher, F.; Hammer, B.; Lauritsen, J. V. (ACS Nano, 2015)

(untitled) - Wang, H.; Zhang, Q.; Yao, H.; Liang, Z.; Lee, H.-W.; Hsu, P.-C.; Zheng, G.; Cui, Y. (Nano Lett., 2014)

(untitled) - Liu, M.; Zhang, C.; Su, J.; Chen, X.; Ma, T.; Huang, T.; Yu, A. (ACS Appl. Mater. Interfaces, 2019)

(untitled) - You, Y.; Ye, Y.; Wei, M.; Sun, W.; Tang, Q.; Zhang, J.; Chen, X.; Li, H.; Xu, J. (Chem. Eng. J., 2019)

(untitled) - Lee, J. S.; Manthiram, A. (J. Power Sources, 2017)

(untitled) - Guo, Y.; Zhang, X.; Zhang, X.; You, T. (J. Mater. Chem. A, 2015)

(untitled) - Chen, B.; Lu, H.; Zhao, N.; Shi, C.; Liu, E.; He, C.; Ma, L. (J. Power Sources, 2018)

(untitled) - Xie, J.; Zhang, H.; Li, S.; Wang, R.; Sun, X.; Zhou, M.; Zhou, J.; Lou, X. W. D.; Xie, Y. (Adv. Mater. (Weinheim, Ger.), 2013)

(untitled) - Zhang, Y.; Yu, S.; Wang, H.; Zhu, Z.; Liu, Q.; Xu, E.; Li, D.; Tong, G.; Jiang, Y. (Chem. Eng. J., 2018)

(untitled) - Liu, K.-K.; Zhang, W.; Lee, Y.-H.; Lin, Y.-C.; Chang, M.-T.; Su, C.-Y.; Chang, C.-S.; Li, H.; Shi, Y.; Zhang, H.; Lai, C.-S.; Li, L.-J. (Nano Lett., 2012)

(untitled) - Wang, C.; Wan, W.; Huang, Y.; Chen, J.; Zhou, H. H.; Zhang, X. X. (Nanoscale, 2014)

(untitled) - Xie, D.; Tang, W.; Wang, Y.; Xia, X.; Zhong, Y.; Zhou, D.; Wang, D.; Wang, X.; Tu, J. (Nano Res., 2016)

(untitled) - Yang, L.; Zhou, W.; Lu, J.; Hou, D.; Ke, Y.; Li, G.; Tang, Z.; Kang, X.; Chen, S. (Nano Energy, 2016)

(untitled) - Dai, X.; Du, K.; Li, Z.; Sun, H.; Yang, Y.; Zhang, W.; Zhang, X. (Int. J. Hydrogen Energy, 2015)

(untitled) - Yue, G.; Ma, X.; Jiang, Q.; Tan, F.; Wu, J.; Chen, C.; Li, F.; Li, Q. (Electrochim. Acta, 2014)

(untitled) - Wang, Y.; Ma, Z.; Chen, Y.; Zou, M.; Yousaf, M.; Yang, Y.; Yang, L.; Cao, A.; Han, R. P. S. (Adv. Mater. (Weinheim, Ger.), 2016)

(untitled) - Wang, J.; Liu, J.; Chao, D.; Yan, J.; Lin, J.; Shen, Z. X. (Adv. Mater. (Weinheim, Ger.), 2014)

(untitled) - Guo, Y.; Gan, L.; Shang, C.; Wang, E.; Wang, J. (Adv. Funct. Mater., 2017)

(untitled) - Zhang, J.; Wang, T.; Pohl, D.; Rellinghaus, B.; Dong, R.; Liu, S.; Zhuang, X.; Feng, X. (Angew. Chem., Int. Ed., 2016)

(untitled) - Xie, D.; Wang, D. H.; Tang, W. J.; Xia, X. H.; Zhang, Y. J.; Wang, X. L.; Gu, C. D.; Tu, J. P. (J. Power Sources, 2016)

(untitled) - Li, X.; Zhao, K.; Zhang, L.; Ding, Z.; Hu, K. (J. Alloys Compd., 2017)

(untitled) - Tan, L.; Li, X.; Wang, Z.; Guo, H.; Wang, J. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Wu, J.; Li, X.; Zeng, H.; Xue, Y.; Chen, F.; Xue, Z.; Ye, Y.; Xie, X. (J. Mater. Chem. A, 2019)